Clone stories: ‘shallow are the souls that have forgotten how to shudder’ - Marks, John (Edinburgh University Press, 2010)
This article explores literary interrogations of the bioethical implications of cloning. It does so by outlining the basic science of cloning before going on to question the dominance of the Freudian notion of the ‘uncanny’ in the critical theoretical responses to cloning by figures such as Jean Baudrillard and Slavoj Žižek. The second half of the article turns to two recent novels exploring the theme of cloning: Eva Hoffman's The Secret, and Kazuo Ishiguro's Never Let Me Go. It is argued that the former rehearses familiar themes of revulsion connected to the figure of the clone, yet resolves the struggle for identity in a ‘human’ conclusion; whereas the latter maintains the uncanny in-human difference of the clone even as it highlights the dangers of the biopolitical instrumentalization of life itself. The article therefore argues that fictional treatments of cloning can provide an important alternative to simplified debates on the subject in the mass media.